Prognostic impact of t(16;21)(p11;q22) and t(16;21)(q24;q22) in pediatric AML: a retrospective study by the I-BFM Study Group - Noort, Sanne; Zimmermann, Martin; Reinhardt, Dirk; Cuccuini, Wendy; Pigazzi, Martina; Smith, Jenny; Ries, Rhonda E; Alonzo, Todd A; Hirsch, Betsy; Tomizawa, Daisuke; Locatelli, Franco; Gruber, Tanja A; et al. (Blood, 2018)
To study the prognostic relevance of rare genetic aberrations in acute myeloid leukemia (AML), such as t(16;21), international collaboration is required. Two different types of t(16;21) translocations can be distinguished: t(16;21)(p11;q22), resulting in the FUS-ERG fusion gene; and t(16;21)(q24;q22), resulting in RUNX1-core binding factor (CBFA2T3). We collected data on clinical and biological characteristics of 54 pediatric AML cases with t(16;21) rearrangements from 14 international collaborative study groups participating in the international Berlin-Frankfurt-Münster (I-BFM) AML study group. The AML-BFM cohort diagnosed between 1997 and 2013 was used as a reference cohort. RUNX1-CBFA2T3 (n = 23) had significantly lower median white blood cell count (12.5 × 109/L, P = .03) compared with the reference cohort. FUS-ERG rearranged AML (n = 31) had no predominant French-American-British (FAB) type, whereas 76% of RUNX1-CBFA2T3 had an M1/M2 FAB type (M1, M2), significantly different from the reference cohort (P = .004). Four-year event-free survival (EFS) of patients with FUS-ERG was 7% (standard error [SE] = 5%), significantly lower compared with the reference cohort (51%, SE = 1%, P < .001). Four-year EFS of RUNX1-CBFA2T3 was 77% (SE = 8%, P = .06), significantly higher compared with the reference cohort. Cumulative incidence of relapse was 74% (SE = 8%) in FUS-ERG, 0% (SE = 0%) in RUNX1-CBFA2T3, compared with 32% (SE = 1%) in the reference cohort (P < .001). Multivariate analysis identified both FUS-ERG and RUNX1-CBFA2T3 as independent risk factors with hazard ratios of 1.9 (P < .0001) and 0.3 (P = .025), respectively. These results describe 2 clinically relevant distinct subtypes of pediatric AML. Similarly to other core-binding factor AMLs, patients with RUNX1-CBFA2T3 rearranged AML may benefit from stratification in the standard risk treatment, whereas patients with FUS-ERG rearranged AML should be considered high-risk.
Keywords: transkriptom; represorové proteiny; Gene Expression Regulation, Leukemic; Male; Chromosomes, Human, Pair 21; retrospektivní studie; Child, Preschool; Adolescent; prognóza; protein PEBP2A2; Child; Infant; Tumor Suppressor Proteins; lidské chromozomy, pár 21; Transcriptome; dítě; akutní myeloidní leukemie; translokace genetická; mužské pohlaví; regulace genové exprese u leukemie; transkripční regulátor ERG; lidské chromozomy, pár 16; nádorové supresorové proteiny; mladiství; předškolní dítě; Chromosomes, Human, Pair 16; Core Binding Factor Alpha 2 Subunit; lidé; protein FUS vázající RNA; ženské pohlaví; Humans; Transcriptional Regulator ERG; kojenec; Repressor Proteins; Translocation, Genetic; Prognosis; Retrospective Studies; Female; RNA-Binding Protein FUS; Leukemia, Myeloid, Acute